Análisis del grado de cumplimiento que tiene el sistema de gestión ambiental NTC-ISO 14001:2015 en las empresas ladrilleras de la ciudad de Neiva - Calderón Pava, Karen Sofia; Reyes Ruiz, Laura Manuela (Universidad Antonio Nariño, 2021)
The present study corresponds to a descriptive-transversal research that associates variables of a quantitative and qualitative type in order to carry out a detailed analysis of the requirements by which brick companies comply with the environmental management system.